(untitled) (Research, Society and Development, 2021)
The puerperal period is the moment of the pregnancy-puerperal cycle that corresponds to the physical regression in pregnancy and the transition to the exercise of motherhood. It starts right after delivery of the placenta and ends around six weeks after delivery, a period marked by several bodily changes and emotional adaptations, which can result in challenges that compromise the mother-child relationship. Nursing care contributes to improvement of this cycle. Analyze the scientific evidence on puerperal care and nursing care; characterize the articles raised. This is an integrative literature review carried out in LILACS and SCIELO databases, accessed by the VHL. Articles that were available electronically, in full, in Portuguese, in the period from 2013 to 2021 were included. The publications, during the analyzed period, were presented in greater quantity in the year of 2013 with 36% of publications. Regarding the SCIELO database, it stood out with 86% of the publications, and regarding the methodological design, 93% of the articles used the quantitative approach. From the analyzed articles, two thematic categories emerged: profile of elderly people residing in long-stay institutions and evaluation of the functional capacity of elderly people in long-stay institutions. Knowing, analyzing and understanding the characteristics of puerperal women, which contributed to deepening the theme and to reflecting on the main points to be evaluated in terms of systematized and individualized care, in order to provide better quality of life for these mothers.